ANALISIS PENGARUH PINJAMAN DARI PIHAK ASING TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Zain Nurwulian; Erni Puji Astutik (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This study aims to analyze the effect of loans from foreign parties on economic growth in Indonesia. This study used a qualitative method with a literature review approach. The results of this study show that economic growth in Indonesia is significantly influenced by loans to foreigners. This loan is used as a source of coffers for development, especially to overcome the imbalance of domestic savings and investment. This loan also helps increase the efficiency, effectiveness and productivity of economic activities for the benefit of the people.